ANALYSIS OF THE IMPACT OF COMPETENCE AND WORK DISCIPLINE ON PATIENT SATISFACTION AT TAMAN HARAPAN BARU HOSPITAL - Ujang Ade Sobarna; Zaharuddin; I Gede Adiputra (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the impact of competence and work discipline on patient satisfaction at Taman Harapan Baru Hospital. The research is motivated by the important role of competence and work discipline in improving patient satisfaction at this institution. A quantitative approach was employed, combining descriptive and verificative methods. Data were collected through questionnaires administered to 50 patients and analyzed using multiple linear regression. The results indicate that both competence and work discipline have a positive and significant effect on patient satisfaction at Taman Harapan Baru Hospital, both partially and simultaneously. The study concludes that enhancing competence and work discipline is essential for optimising patient satisfaction at Taman Harapan Baru Hospital.